The Effect of Work Environment and Job Satisfaction on Employee Performance at Bkd-Psdm Office of Kaur Regency - Albed Alfahmi; Sulisti Afriani; Rina Trisna Yanti (Journal of Indonesian Management, 2021)
This study aims to determine the effect of work environment and job satisfaction on employee performance at the BKD-PSDM Office of Kaur Regency. Samples in this study were 38 employees at the BKD-PSDM Office of Kaur Regency. The data collection used a questionnaire and the analytical method used was multiple linear regression, determination test and hypothesis testing. The results show the regression value Y = 1.054 + 0.686X1 + 0.364X2¬with a positive regression direction, meaning that if the work environment and job satisfaction increased, the performance of employees at the BKD-PSDM Office in Kaur Regency would also increase. The BKD-PSDM office in Kaur Regency, because the significant value of 0.000 is smaller than 0.05. This means that the more the work environment at the BKD-PSDM Office of Kaur Regency increases, the performance will also increase. Job satisfaction has a significant effect on employee performance at the Kaur Regency BKD-PSDM Office, because the significant value of 0.009 is smaller than 0.05. This means that the increase in job satisfaction will increase the performance of the employees of the BKD-PSDM Office of Kaur Regency. The work environment and work satisfaction have a significant effect on employee performance at the BKD-PSDM Office of Kaur Regency because the significant value of 0.000 is smaller than 0.05, thus the initial hypothesis proposed is proven (Ha is accepted). That is, there is a significant effect between work environment and job satisfaction on performance together. The coefficient of determination of R square is 0.618. This means that the work environment and job satisfaction affect performance by 61.8% while the rest (100-61.8% = 38.2%) is effected by other causal factors not examined in this study)